Two new species and new records of terrestrial isopods (Crustacea, Isopoda, Oniscidea) from Brazilian caves - Campos-Filho, Ivanklin Soares; Fernandes, Camile Sorbo; Cardoso, Giovanna Monticelli; Bichuette, Maria Elina; Aguiar, José Otávio; Taiti, Stefano (Zootaxa, 2019)
To date, approximately 190 species of terrestrial isopods are known from Brazil and only 14 are considered troglobiotic. After the examination of a large collection from caves in Bambuí and Una geomorphological areas, along the states of Bahia, Minas Gerais and Goiás, two new troglobiotic species were recognized. Pectenoniscus liliae Campos-Filho, Bichuette & Taiti sp. n. (Styloniscidae) is described from Serra do Ramalho karst area, and Benthana xiquinhoi Campos-Filho, Bichuette & Taiti sp. n. (Philosciidae) from sandstone caves of Chapada Diamantina region. The latter constitutes the second troglomorphic species of the genus. Xangoniscus aganju (Styloniscidae) is also recorded from two caves in the Serra do Ramalho karst area. The systematic position of Iuiuniscus iuiuensis is briefly discussed and Venezillo congener (Armadillidae) is redescribed from São Domingos karst area.